Implementasi Perilaku “MEGERMET” dan Pelatihan Pertolongan Pertama Keracunan Akut Pestisida pada Perempuan Tani di Desa Semangat - Br Karo, Evi Indriani; Nasution, Diah Lestari; Kaban, Febrina Oktavinola (Jurnal Riset Hesti Medan, 2023)
The use of chemical fertilizers (pesticides) is one of the biggest occupational health threats facing by farmer workers, especially women. Improper use of pesticides can have a negative impact on poisoning users. The lack of awareness about the negative effects of chronic diseases caused by exposure to pesticides, lack of information about the risks of using pesticides, resulting in pesticides being often used irresponsibly and inappropriately, both the dosage and practice of using them are inappropriate and unsafe and farmers often do not wear appropriate Personal Protective Equipment (PPE) when using pesticides. This community service aims to improve the health quality of the women farmers in the Semangat village through the implementation of "MEGERMET" behaviours and first aid training for acute pesticide poisoning. The methods used are conducting socialization, health checks, health education about pesticides and their impact on health, procedures to use pesticides correctly through "MEGERMET" behavior, demonstrations how to use personal protective clothing  and Personal Protective Equipment (PPE) as well as first aid training on acute pesticide poisoning especially for women who are members of a farmer community in Semangat village. The results of this community service activity shows that there is an increase in the knowledge among women farmers in how to use pesticide safely and properly by 80%, the women farmers at Semangat village are able to implement "MEGERMET" behaviour as a procedure for using pesticides wisely and 80% of women at Semangat village are able to provide first aid for acute pesticide poisoning. Forming an occupational health forum (“Pos UKK”) is believe to be able to continue encouraging women farmer behaviour at Semangat village to improve health and reducing the risk of using pesticides.